Potensi Interaksi Obat Pada Pasien Gangguan Ginjal Kronis di Instalasi Rawat Inap RSUD Dr. Moewardi Tahun 2014 - Khasanah, Rizqi Nurul (2016)
Chronic kidney disease (CKD) is a condition which characterized by a gradual loss of kidney function accompanied by manifestations of kidney pathology abnormality for at least three months. Patients with chronic kidney disease who have some complications usually use various drug combinations. The use of drugs combination can increase the occurrence of drug interaction. The purpose of this study was to find out the potential drug interaction that may occured in hospitalized patients with chronic kidney disease at "X" hospital in 2014. This study is a non-experimental research in which the data analysis was done by collecting the medical records retrospectively. The samples were the hospitalized patients with chronic kidney disease at "X" hospital in 2014. The data were analyzed descriptively. The sampling technique was done by purposive sampling method. There were 100 patients obtained for this study. Out of 100 patients, there were 84 patients (84%) who had a potential drug interaction with 336 cases of drug interactions. The result obtained based on the drug interaction mechanism were 44.94% pharmacodynamics mechanism, 29.76% pharmacokinetic mechanism, and 25.29% unknown mechanism. The result obtained based on drug interactions seriousness were 63.98% moderate drug interaction, 29.46% minor drug interaction and 6.55% major drug interaction. The most common drug interaction happened in "X" hospital in 2014 were furosemide and ceftriaxone in 27 cases which is categorized as moderate interactions.